Pengembangan Modul Elektronik Berbantuan Aplikasi Flipping Book PDF Professional Pembelajaran Menulis Teks Eksplanasi - Yulia Marizal; Yasnur Asri (Diglosia: Jurnal Kajian Bahasa, Sastra, dan Pengajarannya, 2022)
This research was conducted to overcome the limitations of teaching materials in explanatory text learning. This study aims to describe the process of developing a valid, practical, and effective electronic module for learning to write explanatory text assisted by the Flipping Book PDF Professional application, which class XI Vocational School students use. This type of research is research and development (research and development). The development model is 4-D, defining, designing, developing, and deploying. The research subjects were class XI PH 1 SMK Negeri 9 Padang students, totaling 30 people. The results showed that the electronic module product, with the help of the Flipping Book PDF Professional application developed, got valid data from the validator with an average of 96.17% in the very valid category. This product is also considered efficient, with an average of 91.66% from teachers in the efficient category and 86.38% from students in the efficient category. In addition, this product can also increase the value of student learning outcomes. In the knowledge test, the average score was 87% with an "A" predicate, while in the skill test, an average was 88.22% with an "A" predicate. Then, the assessment of student attitudes when studying got an average of 91.33% with an "A" predicate.